Two new metazoans from the Cambrian Guanshan biota of China - Zhao, Jun; Li, Yujing; Selden, Paul A. (Frontiers in Ecology and Evolution, 2023)
Sessile epibenthos were diverse and played important part in the process of energy flow in the Cambrian marine ecosystem. Based on new specimens from the Gaoloufang Section of the Wulongqing Formation, we describe two new representatives of the group that show character traits with cnidarians and bryozoans. If confirmed, the new material can help us understand the origin and early evolution of these two phyla. The discovery of more sessile epibenthos suggests that the benthic ecosystem of the Guanshan biota (Cambrian Series 2, Stage 4) is more diverse than previously thought.